A new combination in Tulista, T. kingiana (Asphodeloideae, Xanthorrhoeaceae / Alooideae, Asphodelaceae) - Smith, Gideon F.; Figueiredo, Estrela; Molteno, Steven (Phytotaxa, 2017)
Phylogenetic studies in the Xanthorrhoeaceae subfam. Asphodeloideae (alternatively Asphodelaceae subfam. Alooideae) (Treutlein et al. 2003a, b; Grace et al. 2013; Manning et al. 2014) indicated that the genus Haworthia Duval (1809: 7) sensu lato should be split into three genera. The three haworthioid genera established and widely accepted for the three groups of species are: Haworthia sensu stricto, Haworthiopsis Rowley (2013: 4), and Tulista Rafinesque (1840: 137). In terms of number of species, Tulista is the smallest of the three genera and is widely considered to include five species. For four of these, T. marginata (Lamarck 1783: 89) Rowley (2013: 6), T. minima (Aiton 1789: 468) Boatwright & Manning in Manning et al. (2014: 70), T. opalina (Hayashi 2001: 17) Breuer (2016: 7), and T. pumila (Linnaeus 1753: 322) Rowley (2013: 6), combinations have been validly published. However, for the fifth species, Haworthia kingiana Von Poellnitz (1937: 203), a valid combination has yet to be published in Tulista. We do so here.